An Analysis of Business Licensing Policy Implementation of Batamâs One Stop Service (OSS) and Lessons Learned from Singaporeâs Online Business Licensing Service (OBLS) - Eva Metika Sihombing, Mrs. (Jurnal Ilmiah Administrasi Publik, 2012)
Indonesia is endeavouring to boost its economic growth by improving business climate. However, facts (from Doing Business 2012): Indonesia ranked poorly, 129th in Ease of Doing Business, 155th in Starting Business among 183 economies; 19th and 21st in East Asia and Pacific (out of 24 economies). Establishing One Stop Service (a center to obtain various business licenses) in every region is one of the ways to improve the business climate. One of such centres has been implemented in Batam. But facts (from Doing Business 2012) indicated that Batam ranked 15th in Starting Business among 20 regions in Indonesia. On the other hand, Singapore having an integrated online system of business licensing service called Online Business Licensing Service has been ranked by the same measurement 1stin Ease of Doing Business and 4th in Starting Business. The two types of business licensing services are different in their implementation. Implementation is an important stage in policy analysis. Besides, by analysing the implementation of a policy, constraining and supporting factors may be found. Thus, this paper seeks to analyse the implementation of Batamâs OSS and look into the successful implementation of Singaporeâs OBLS which can be taken as lessons for the future improvement of Batamâs OSS Implementation.